KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI MEDIA AUDIO VISUAL PADA CERITA PENDEK DI SDN 42 PRABUMULIH - Meisya Sari, Wayan; Octaria, Dina; Masnunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe students' creative thinking skills through audio-visual media on short stories in IV SDN 42 Prabumulih in the even semester of the 2023/2024 school year. The method used is a quantitative experimental method with a quantitative descriptive approach in a pre-experimental one shot case study design. The sample of this research is class IV which consists of 27 students. Data collection techniques are tests and documentation. Data analysis techniques using descriptive analysis with scoring guidelines for creative thinking ability indicators. Based on the results of the student's creative thinking ability test through the test, it was obtained that a total of 45% (12 students) were in the very creative category, 48% (13 students) were in the creative category and 7% (2 students) in the moderately creative category with the average value of the student's creative thinking ability test was 80.44. This shows that students' creative thinking skills through audio-visual media on class IV short stories at SDN 42 Prabumulih are categorized as Creative.